2013
DOI: 10.1038/ismej.2013.150
|View full text |Cite
|
Sign up to set email alerts
|

Community history affects the predictability of microbial ecosystem development

Abstract: Microbial communities mediate crucial biogeochemical, biomedical and biotechnological processes, yet our understanding of their assembly, and our ability to control its outcome, remain poor. Existing evidence presents conflicting views on whether microbial ecosystem assembly is predictable, or inherently unpredictable. We address this issue using a well-controlled laboratory model system, in which source microbial communities colonize a pristine environment to form complex, nutrient-cycling ecosystems. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
103
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 47 publications
(57 reference statements)
1
103
0
1
Order By: Relevance
“…This is particularly important in soils, which exhibit a very high species turnover rate: in one case, the bacterial and archaeal ammonia oxidizing communities in a range of Dutch agricultural soils showed above 50% change in community structure between seasons [61,62]. In another, it was shown that when colonizing a novel environment, the microbial community undergoes drastic rearrangement, and draws heavily from members of the 'rare biosphere' [9,63], a strategy which may be crucial for stressresponse [51].…”
Section: Long-term Effects: Stability and Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important in soils, which exhibit a very high species turnover rate: in one case, the bacterial and archaeal ammonia oxidizing communities in a range of Dutch agricultural soils showed above 50% change in community structure between seasons [61,62]. In another, it was shown that when colonizing a novel environment, the microbial community undergoes drastic rearrangement, and draws heavily from members of the 'rare biosphere' [9,63], a strategy which may be crucial for stressresponse [51].…”
Section: Long-term Effects: Stability and Resiliencementioning
confidence: 99%
“…Specifically, in microbial systems, where diversity and abundance are extreme and growth rates are rapid, it was formerly assumed that redundancy is so high that diversity and community composition are decoupled from functioning due to the following observations: 1) most microbial species are ubiquitous and present in very low densities, awaiting an opportunity to "bloom"; 2) the rapid adaptability of microbes means that such a system will never be so impoverished as to cease functioning; and 3) the microbial system is so tightly linked to its physical environment that it cannot be studied within the context of cause-effect that is generally necessary for BEF studies. However, recent studies have shown that community composition matters to function [5,6]: in soil, microbial communities exhibit a home-field advantage in decomposing endemic vs. foreign litter [7,8] and different communities do not become more similar when exposed to the same environment [9]. This ongoing discussion has been particularly important in the realm of ecosystem models, where stable physical parameters or very coarse microbial parameters (such as total biomass) are assumed to accurately represent microbial contributions to ecosystem function [10].…”
Section: Introductionmentioning
confidence: 99%
“…This causes that some ecosystems are functioning properly only in the original environment which is caused by coevolution of microorganisms and their adaptation to environmental conditions (Keiser et al 2011). Moreover, one of the studies has shown that different microbial communities have not become similar under the same conditions, suggesting that the original composition of microorganisms could be a predictor of the responses of a particular ecosystem and its development (Pagaling et al 2014). For that reason, it is increasingly common to classify microorganisms communities not on the basis of their taxonomic affiliation but on their functions.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, nutrient supply may be unpredictable, nutrient and biomass removal rates may not balance, and population sizes may be small so that random fluctuations due to birth and death events play an important role. Recent studies have shown that microbial communities can undergo unpredictable divergence from similar initial conditions [1], dramatic fluctuations in species composition [2] and even chaotic dynamics [3][4][5][6]. Stochastic models for microbial ecosystem dynamics will be needed to obtain detailed understanding of such results.…”
Section: Introductionmentioning
confidence: 99%